2019
DOI: 10.1080/14786419.2019.1586697
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Glehnia littoralis and their chemotaxonomic significance

Abstract: Phytochemical investigation of the roots of Glehnia littoralis Fr. Schmidt. ex Miq. led to the isolation of 16 known compounds, including three β-carboline alkaloids (1-3), four phenylpropanoids (4-7), five phenolic acids (8-12), three polyacetylenes (13-15) and one fatty acid ( 16). The structures of these compounds were elucidated on the basis of spectral analysis and comparison with those reported in literatures. To the best of knowledge, the report of the first β-carboline alkaloid in the Umbelliferae fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…e results showed that the total content of these three coumarins was the highest in fruit (0.6364 mg•g − 1 ), which was 8.24 times higher than that of roots and 42.15 times higher than that of leaves [75]. In another study, Xin et al (2009) compared the coumarin content in the roots of G. littoralis in four different harvesting periods (September 15, September 30, October Evidence-Based Complementary and Alternative Medicine 4 Evidence-Based Complementary and Alternative Medicine 6 Evidence-Based Complementary and Alternative Medicine Dried roots [19] (S)-Phenyllactic acid methyl ester (2) Dried roots [19] Caffeic acid 3Dried root, dried underground parts [38,39] Chlorogenic acid (4) Dried root, dried underground parts [38,39] Ferulic acid (5) Dried root, dried underground parts [38][39][40] 3-Methoxy-4-β-D-glucopyranosyloxypropiophenone (6) Dried underground parts, dried roots bark [39,41] 4…”
Section: Coumarinsmentioning
confidence: 99%
See 4 more Smart Citations
“…e results showed that the total content of these three coumarins was the highest in fruit (0.6364 mg•g − 1 ), which was 8.24 times higher than that of roots and 42.15 times higher than that of leaves [75]. In another study, Xin et al (2009) compared the coumarin content in the roots of G. littoralis in four different harvesting periods (September 15, September 30, October Evidence-Based Complementary and Alternative Medicine 4 Evidence-Based Complementary and Alternative Medicine 6 Evidence-Based Complementary and Alternative Medicine Dried roots [19] (S)-Phenyllactic acid methyl ester (2) Dried roots [19] Caffeic acid 3Dried root, dried underground parts [38,39] Chlorogenic acid (4) Dried root, dried underground parts [38,39] Ferulic acid (5) Dried root, dried underground parts [38][39][40] 3-Methoxy-4-β-D-glucopyranosyloxypropiophenone (6) Dried underground parts, dried roots bark [39,41] 4…”
Section: Coumarinsmentioning
confidence: 99%
“…So far, ten phenylpropanoids, including six phenylpropionic acid (1-5, 10), three phenylpropanal (6)(7)(8), and one phenylpropanol (9) were isolated from G. littoralis. Furthermore, Zhang et al isolated and identified two simple phenyllactic acid compounds (S)-phenyllactic acid (1) and (S)-phenyllactic acid methyl ester (2) via spectral analysis of ethanol extract from the root of G. littoralis [19]. It is worth noting that these compounds were isolated from the plant for the second time when studying their taxonomic significance, suggesting that these compounds may be useful chemical taxonomic markers for G. littoralis.…”
Section: Phenylpropanoids Phenylpropanoids Widely Exist In Nature Imentioning
confidence: 99%
See 3 more Smart Citations